Clinicopathological significance and potential drug target of CDH1 in breast cancer: a meta-analysis and literature review - Huang, Ruixue (Drug Des Devel Ther, 2015)
CDH1, as a tumor suppressor gene, contributes sporadic breast cancer (BC) progression. However, the association between CDH1 hypermethylation and BC, and its clinicopathological significance remains unclear. We conducted a meta-analysis to investigate the relationship between the CDH1 methylation profile and the major clinicopathological features. A detailed literature was searched through the electronic databases PubMed, Web of Science™, and EMBASE™ for related research publications. The data were extracted and assessed by two reviewers independently. Odds ratios (ORs) with corresponding confidence intervals (CIs) were calculated and summarized respectively. The frequency of CDH1 methylation was significantly higher in invasive ductal carcinoma than in normal breast tissues (OR =5.83, 95% CI 3.76–9.03, P<0.00001). CDH1 hypermethylation was significantly higher in estrogen receptor (ER)-negative BC than in ER-positive BC (OR =0.62, 95% CI 0.43–0.87, P=0.007). In addition, we found that the CDH1 was significantly methylated in HER2-negative BC than in HER2-positive BC (OR =0.26, 95% CI 0.15–0.44, P<0.00001). However, CDH1 methylation frequency was not associated with progesterone receptor (PR) status, or with grades, stages, or lymph node metastasis of BC patients. Our results indicate that CDH1 hypermethylation is a potential novel drug target for developing personalized therapy. CDH1 hypermethylation is strongly associated with ER-negative and HER2-negative BC, respectively, suggesting CDH1 methylation status could contribute to the development of novel therapeutic approaches for the treatment of ER-negative or HER2-negative BC with aggressive tumor biology.